(untitled) (Global Journal of Human-Social Science, 2019)
The issue of economic transition in Algeria was reviewed in this paper. The actions taken by the government to speed up the transition process were examined in light of whether the State was able to move away from protecting old premises of the ’rentier state’ and establish a free and productive economic system. The review revealed the contradictions that the planning system of the 1970s had produced and how they eventually led to a transitional crisis. The other finding was that the effectiveness of the transitional institutions, laws, mechanisms, and the dynamism of country’s external trade sector were undermined by the inconsistencies of contradictory and often overlapping privatization schemes, the predatory nature of the existing private sector, and the country’s imbalanced external trade and finance. The third finding was that the ’national natural resources doctrine’ sustained the mechanisms of the ’rentier state’ and became a major obstacle to easing up the economic transitional process.